The Effect of Antenatal Care During Covid -19 on Complications of Pregnant - Ni Gusti Made Ayu Agung Budhi; Maryanah Maryanah (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Quality Antenatal Care (ANC) services can prevent complications during pregnancy, but during the Covid-19 pandemic, there is a policy for mothers to postpone ANC visits. The purpose of the study was to find out how the influence of ANC services during the Covid-19 pandemic on the incidence of complications in pregnant women. The research method used is an analytical survey with a Cross-Sectional approach. The number of samples is 110 pregnant women respondents. The statistical test used is the Chi-Square test. The results showed that the age of pregnant women was 92.1% of healthy reproductive age, high school education level was 90.4%, some pregnancies experienced by mothers 2 were 66.7%, work as housewives were 67%. The biggest complication that occurs in pregnant women is anemia (40%). The provision of quality ANC services with 10T has a positive influence on the incidence of complications in pregnancy during the pandemic (p-value <0.05), as well as understanding of the Maternal and Child Health (MCH) book (p-value <0.05) and the anxiety felt by the mother (p-value <0.05) influences the occurrence of complications. The conclusions obtained were the effect of providing quality ANC services with 10 T, understanding of the MCH handbook on the incidence of complications during the covid-19 pandemic.